Synergies in the ground reaction forces and moments during double support in curb negotiation in young and older adults - Cui, Chuyi; Kulkarni, Ashwini; Rietdyk, Shirley; Barbieri, Fabio A. [UNESP]; Ambike, Satyajit (Elsevier, 2020)
Falls that occur while negotiating steps are a leading cause of death in older adults. Although recent efforts have improved understanding of the mechanics and control of stepping behaviors, the double support phase during stepping is understudied. Therefore, we quantified the stability of the resultant forces and moments acting on the body during this phase. These quantities determine the movement of the body, and therefore, their stability is essential for successful stepping behavior. We measured the ground reaction variables (GRVs) under both feet as healthy young (n = 10) and older adults (n = 10) stepped up and down a curb. We employed the uncontrolled manifold method to evaluate the hypotheses that the GRVs covary to stabilize the resultant force and moment in the three coordinate directions. Robust stabilization of the resultant forces and moments was observed while stepping up. However, while stepping down, the stability of the resultant moment was prioritized over that of the resultant forces in the vertical and the anterior-posterior directions, and the stability of the resultant medio-lateral force was prioritized over that of the resultant anterior-posterior force. The salience of stabilizing whole-body angular momentum and medio-lateral motion during locomotion is well known, but their prioritization during adaptive gait is a novel result and is possibly related to the higher likelihood of falling during descent (versus ascent). Finally, contrary to our expectations, we observed no age differences in our stability indices, indicating that healthy aging does not diminish the stability of the resultant forces and moments.
Keywords: Adaptive gait; Aging; Uncontrolled manifold analysis